Iran: International community must stand with women and girls suffering intensifying oppression - Amnesty International (Amnesty International, 2023)
The Iranian authorities are doubling down on their oppressive methods of policing and severely oppressing Iranian women and girls for defying degrading compulsory veiling laws, Amnesty International said today. In a detailed analysis published today, the organization exposes the authorities’ intensified nationwide crackdown on women and girls who choose not to wear headscarves in public.
Keywords: 2023-07 July